Radiation climate of New Delhi Part II : Longwave radiation and energy budget - LETTAU, KATHARINA (MAUSAM, 1971)
Monthly budgets of long wave short wave, and net radiation, separate for air-space and air-soil interfaces, and also for the atmospheric column, are presented for the years 1964 and 1965 at New Delhi. A combination of direct radiation measurements at Lodi Rd. Observatory, New Delhi evaluations of satellite based scannings of the region, and climatonomical theories (as developed by H. Lettau), yields the monthly budgets of latent and sensible heat. Radiative shortwave heating and longwave cooling rates for the local atmospheric column are summarised for the seasons, resulting in a mean annual net cooling rate of 0. 4°C in both years. In this climate where the seasonal maximum of precipitation coincides closely with that of. insolation, the moisture budget at the air-soil Interface shows that about 80 per cent of the annual evaporation occurs from July to September In both years. Surface runoff appears to be restricted to the monsoon season and amounts to less than evapotranspiration even in the wettest month. Calculated values of exchangeable soil moisture were about twice as high in 1964 than in 1965 due to the intensive monsoon. The carry-over into the following dry season was considerable. Net moisture import (horizontal advection) into the atmospheric column over New Delhi was more than five times higher during the summer of 1964 than of 1965. The change over from moisture import to moisture export occurs abruptly with the greatest drop during October in both years. The calculation of a complete energy budget for the soil-air interface shows that due to the great demand of energy for evapotranspiration, monthly means of sensible heatflux, normally directed from the ground into the air during summer, can be reversed resulting in 'psychrometric cooling' of the ground. In 1964, such reversal occurred from July to September, but in 1965 it was weak and restricted to the month of September. Accordingly, the monthly mean surface temperature dropped from June to July by 10°Cin 1964, but only by 60Cin 1965. Flux of sensible heat from and into the soil reaches extremes in December and April, respectively, but turned out to be small in comparison with other constituents of the monthly heat budget. With the aid of the 'climatonomical' analysis method it is possible to establish quantitatively the constituent terms of the energy budget. For the atmospheric column, however, the energy supplied by advection cannot be separated from the contribution by subsidence. Considering the importance attributed to subsidence for maintaining arid conditions over northwestern India, a supplementary synoptic-aerological analysis of the atmospheric circulation over the region appears to be desirable in order to separate the effects of the two processes in the course of the year.